ANALYSIS OF INDIVIDUAL AND STRUCTURAL POVERTY IN URBAN (CASE STUDY IN SEMANGGI VILLAGE) - Nurhayati Nurhayati; Vincent Hadi Wiyono; Aria Ganna Henryanto (MESP–FEB UNS, 2023)
This article aims to identify several individual and structural factors that are thought to be explanations for the phenomenon of urban poverty. This study uses mixed research methods, namely by combining quantitative and qualitative research. Based on a household census conducted in the two poorest and richest RTs in the poorest RW in Semanggi Sub-District, this research found that first, individual poverty occurs due to low levels of education which have an impact on low-paid jobs, early marriage and a tendency to have more children. Second, structural poverty occurs as a result of illegal residence status which results in limited access to available public services. Moreover, the social safety net programs in the form of Raskin and Raskinda, for example, are distributed equally among all residents, as a result the target households do not really benefit from the program.